2017
DOI: 10.1002/mde.2842
|View full text |Cite
|
Sign up to set email alerts
|

How Strategic Groups Act Competitively Within and Across Markets

Abstract: Our study analyzes rivalry within and across markets of size-defined strategic groups in the banking industry. We consider that, owing to group-level effects, like efficiency and funding, the degree of rivalry of size-defined strategic groups depends on whether the competitor is acting in the same or in a different market and whether the competing firms are within the same strategic group or in different groups. We estimate the effect of group interactions within and across loans and deposits markets on firm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We illustrate the proposed BHMM in the public banking industry. Because of its strategic and economic significance, banking has served as a research context for several studies on various sources of intra-industry competitive heterogeneity (DeSarbo and Grewal, 2008; DeSarbo et al , 2010; Ebbes et al , 2010; Mas-Ruiz and Ruiz-Moreno, 2011, 2017; Mas-Ruiz et al , 2014; McNamara et al , 2003; Penagos-Londoño and Ruiz-Moreno, 2019). Also, the banking sector represents a turbulent environment with fuzzy boundaries where identifying its competitive groups is a nontrivial problem (DeSarbo et al , 2009).…”
Section: Empirical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We illustrate the proposed BHMM in the public banking industry. Because of its strategic and economic significance, banking has served as a research context for several studies on various sources of intra-industry competitive heterogeneity (DeSarbo and Grewal, 2008; DeSarbo et al , 2010; Ebbes et al , 2010; Mas-Ruiz and Ruiz-Moreno, 2011, 2017; Mas-Ruiz et al , 2014; McNamara et al , 2003; Penagos-Londoño and Ruiz-Moreno, 2019). Also, the banking sector represents a turbulent environment with fuzzy boundaries where identifying its competitive groups is a nontrivial problem (DeSarbo et al , 2009).…”
Section: Empirical Studymentioning
confidence: 99%
“…The diversity in the strategy and performance of the firms within the same industry is addressed vis a vis intra-industry competitive heterogeneity (DeSarbo et al , 2010; Noda and Collis, 2001). Researchers have addressed intra-industry competitive heterogeneity based on three different perspectives: strategic groups (Ebbes et al , 2010; Mas-Ruiz and Ruiz-Moreno, 2017), performance groups ( Wiggins and Ruefli, 1995) and impact groups (DeSarbo et al , 2007; Murthi et al , 2013). DeSarbo et al (2010) developed the framework of competitive groups and showed how traditional conceptualizations via solely strategic, performance or impact groups are inadequate to represent intra-industry competitive heterogeneity fully.…”
Section: Introductionmentioning
confidence: 99%
“…marginal operating costs of loans; and SD24it: marginal operating costs of deposits. Because a bank's marginal cost is also part of the Lerner indices, we consider a translog function (Mas-Ruiz & Ruiz-Moreno 2017). This functional form is common in the analysis of banking markets because it deals with economies of scale and scope in multiproduct firms.…”
Section: Sample and Variablesmentioning
confidence: 99%